RETRACTED: Rhodomyrtus tomentosa as a new anticancer molecular strategy in breast histology via Her2, IL33, EGFR, and MUC1 - Situmorang, Putri Cahaya; Ilyas, Syafruddin; Syahputra, Rony Abdi; Sari, Reka Mustika; Nugraha, Alexander Patera; Ibrahim, Alek (Frontiers in Pharmacology, 2024)
The prevalence of breast cancer among patients in Indonesia is significant. Indonesian individuals maintain the belief that cancer cannot be cured alone by pharmaceuticals and treatment; herbal remedies must be used in conjunction. Rhodomyrtus tomentosa, also known as Haramonting, is an indigenous Indonesian medicinal plant renowned for its copious antioxidant properties. The objective of study was to assess the impact of haramonting on breast cancer by examining the expression of various biomarker proteins associated with breast cancer. Haramonting was administered to breast cancer model mice at different doses over a period of 30 days. Subsequently, blood and breast samples were obtained for immunohistochemistry and enzyme-linked immunosorbent assays (ELISA). Authors have discovered that there has been a notable rise in the proliferation of epithelial cells in the duct lobes, resulting in the formation of ducts and lobules. Additionally, the researchers discovered that the breasts exhibited distinct clinical and histological alterations. Haramonting possesses the capacity to restore the concentrations of malondialdehyde (MDA) and superoxide dismutase (SOD) to normal levels in the blood serum of rats afflicted with cancer. The histopathological analysis of the breast tissue revealed elevated levels of Her2, IL33, EGFR, and MUC1. The authors also discovered a notable increase in the growth of epithelial cells, with two or more layers of cells reaching towards the centre of the duct. The size of the epithelial cells exhibits variability; however, this state ameliorates with the administration of a dosage of 300 mg/kgBW of this botanical specimen. This study proposes that Haramonting may be effective in treating breast cancer.